The Contemporary Approach to the Study of the Social and Economic Category of State-Owned Property - P S Ivanychev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2010)
The article offers the insight into the synthetic approach to the study of state property within the sociological perspective. Various approaches to the study of property are scrutinized: the Marxist, the private-public, the functional, the institutional and the contemporary synthetic one. The necessity for the investigation of state property as a system of social institutions is asserted. The potentialities of social regulation of state property are identified in this very item.